2012
DOI: 10.1177/0004867411430877
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma increases the risk of post-traumatic stress disorder in response to first-episode psychosis

Abstract: These results suggest the cognitive, social and biological consequences of childhood trauma can prevent effective recovery from the trauma of acute first-episode psychosis resulting in post-psychotic PTSD. Treatment strategies for post-psychotic PTSD must address childhood trauma and related PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 23 publications
6
77
0
1
Order By: Relevance
“…Prolonged experience of psychotic symptoms may also be seen as an ongoing trauma (Bendall et al, 2006). Second, the experience of childhood trauma has been found to render people more vulnerable to developing PTSD following an acute psychosis (Bendall et al, 2012), which also concurs with the earlier mentioned dose-response effect (Trauelsen et al, 2015). Finally, as mentioned earlier, the presence of comorbid PTSD can exacerbate psychotic symptoms and increase the risk of relapse.…”
supporting
confidence: 73%
“…Prolonged experience of psychotic symptoms may also be seen as an ongoing trauma (Bendall et al, 2006). Second, the experience of childhood trauma has been found to render people more vulnerable to developing PTSD following an acute psychosis (Bendall et al, 2012), which also concurs with the earlier mentioned dose-response effect (Trauelsen et al, 2015). Finally, as mentioned earlier, the presence of comorbid PTSD can exacerbate psychotic symptoms and increase the risk of relapse.…”
supporting
confidence: 73%
“…Addressing trauma identified by instruments such as the TEC could have clinical relevance, as the presence of childhood trauma appears to raise the possibility of post-psychosis posttraumatic stress disorder (Bendall et al, 2012). The consequences of childhood/adolescent trauma are far-reaching, and the TEC might be useful for a number of research questions, and potentially also for informing how we can improve recovery outcomes for young people with early-course psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, over 17 studies have reported high rates of post-psychotic PTSD symptoms related to these experiences. These 17 studies have included 760 participants, primarily composed of non-affective psychotic disorders (2, 6, 10, 11, 1527). Using a variety of assessment methods among inpatients and outpatients with psychosis, participants have been asked to respond to the questions based on their reactions toward potentially frightening psychotic symptoms and/or treatment experiences (i.e., negative aspects of treatment).…”
Section: Introductionmentioning
confidence: 99%